2011
DOI: 10.1371/journal.pone.0029634
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Vitamin D Receptor Polymorphisms in Head and Neck Squamous Cell Carcinoma

Abstract: BackgroundIn patients with advanced non-small-cell lung cancer, vitamin D receptor (VDR) polymorphisms and haplotypes are reported to be associated with survival. We hypothesized that a similar association would be observed in patients with head and neck squamous-cell carcinoma (HNSCC).MethodsIn a post-hoc analysis of our previous prospective cohort study, VDR polymorphisms including Cdx2 G/A (rs11568820), FokI C/T (rs10735810), BsmI A/G (rs1544410), ApaI G/T (rs7976091), and TaqI T/C (rs731236) were genotyped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…As vitamin D metabolism involves many regulatory genes it is not unexpected that the same GSVs would result in the same direction of associations for each disease outcome. Similar results were also found in other studies on cancer outcome18 and risk 40. In one study, VDR sequence variants and haplotypes suggested an association may exist with progression‐free survival in a cohort of Japanese with HNC,18 although the sample size was not large enough to draw definitive conclusions.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…As vitamin D metabolism involves many regulatory genes it is not unexpected that the same GSVs would result in the same direction of associations for each disease outcome. Similar results were also found in other studies on cancer outcome18 and risk 40. In one study, VDR sequence variants and haplotypes suggested an association may exist with progression‐free survival in a cohort of Japanese with HNC,18 although the sample size was not large enough to draw definitive conclusions.…”
Section: Discussionsupporting
confidence: 82%
“…However, vitamin D may play a different role in disease initiation compared to disease progression, and GSVs that predict disease outcomes may be different than those that predict disease risk. There are many reports suggesting that vitamin D can reduce tumor growth of HNC in vitro and in vivo 18. Research has shown GSVs in vitamin D metabolism pathway in several cancers could modify the disease outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hama et al reported the VDR FokI TT genotype was associated with a poor progression-free survival rate in patients with head and neck squamous cell carcinoma. In contrast, the other polymorphisms (BsmI, ApaI, and TaqI) showed no significant associations with progression-free survival [35]. In this study, we did not perform prognostic analyses; however, we found that the TT genotype carriage of TaqI polymorphisms was associated with advanced tumor stage, worse tumor differentiation, presence of cirrhosis, and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 60%
“…We used polymerase chain reaction and direct sequencing to analyze VDR polymorphisms according to the Fok I single nucleotide polymorphisms as described previously [15].…”
Section: Methodsmentioning
confidence: 99%